17β-Estradiol Concentration and Direct β2-Adrenoceptor Inhibition Determine Estrogen-Mediated Reversal of Adrenergic Immunosuppression. Issue 1 (January 2022) - Priyanka, Hannah P.; Thiyagaraj, A.; Krithika, G.; Nair, R. S.; Hopper, W.; ThyagaRajan, S.
Background: Sympathetic innervation of lymphoid organs, and the presence of 17β-estradiol (estrogen or E2) and adrenergic receptors (ARs) on lymphocytes, suggests that sympathetic stimulation and hormonal activation may influence immune functions. Purpose: Modeling and simulating these pathways may help to understand the dynamics of neuroendocrine-immune modulation at the cellular and molecular levels. Methods: Dose- and receptor-dependent effects of E2 and AR subtype-specific agonists were established in vitro on lymphocytes from young male Sprague-Dawley rats and were modeled in silico using the MATLAB Simbiology toolbox. Kinetic principles were assigned to define receptor–ligand dynamics, and concentration/time plots were obtained using Ode15s solvers at different time intervals for key regulatory molecules. Comparisons were drawn between in silico and in vitro data for validating the constructed model with sensitivity analysis of key regulatory molecules to assess their individual impacts on the dynamics of the system. Finally, docking studies were conducted with key ligands E2 and norepinephrine (NE) to understand the mechanistic principles underlying their interactions. Results: Adrenergic activation triggered proapoptotic signals, while E2 enhanced survival signals, showing opposing effects as observed in vitro. Treatment of lymphocytes with E2 shows a 10-fold increase in survival signals in a dose-dependent manner. Cyclic adenosine monophosphate (cAMP) activation is crucial for the activation of survival signals through extracellular signal-regulated kinase (p-ERK) and cAMP responsive element binding (p-CREB) protein. Docking studies showed the direct inhibition of ERK by NE and β2-AR by E2 explaining how estrogen signaling overrides NE-mediated immunosuppression in vitro. Conclusion: The cross-talk between E2 and adrenergic signaling pathways determines lymphocyte functions in a receptor subtype and coactivation-dependent manner in health and disease.